Analisis Kompetensi Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Guru Bahasa Arab Madrasah Tsanawiyah - Suyatno Suyatno (Balai Diklat Keagamaan Semarang, 2020)
A teacher is required to draw up a Learning Implementation Plan based on syllabus and basic competencies. Arabic Language Teachers are still unable to understand the preparation of the Learning Implementation Plan. This qualitative descriptive study measures the ability of the training participants who are nota bene are Arabic language teachers at the Tsanawiyah level in preparing the Learning Implementation Plan. The primary data used is the Learning Implementation Plan document prepared by the training participants. Learning Implementation Plans made by participants were analyzed through eight components. By analyzing the data collected by taking into account the drafting instructions, it was found that from the eight components or aspects studied in the preparation of the Learning Implementation Plan, it was found that only the components composing the learning steps, participants got the title of being able to. There are three components of participants getting the title of capable enough, the other components getting the title of underprivileged. Thus it can be concluded that the participants of the substantive technical training of Arabic teachers in 2019, are less capable in preparing the Learning Implementation Plan.